15. IMAGING CHARACTERISTICS AND VALUE OF ULTRASOUND AND X-RAY IN THE DIAGNOSIS OF MIDGUT VOLVULUS/ INTESTINAL MALROTATION IN NEONATES (Vietnam Journal of Community Medicine, 2023)
Purpose: To describe the imaging characteristics and evaluate the value of ultrasound and X-ray in diagnosing midgut volvulus/intestinal malrotation in neonates. Material and methods: Retrospective cross-sectional description of 250 patients treated in NCH with symptoms of suspected intestinal volvulus, in which 50 patients underwent emergency surgery due to midgut volvulus/intestinal malrotation and 200 patients underwent emergency surgery due to other diseases such as small bowel obstruction, duodenal obstruction, necrotizing enterocolitis. The patients performed abdominal ultrasounds or X-rays before surgery. Result: The most common sonographic findings were whirlpool sign (52.1%) and SMV/SMA inversion (50%). The most common findings on the UGI series were an abnormal position of DJJ (96.3%) and an abnormal position of jejunal loops (63%), the corkscrew sign is rare (0%). The sensitivity and specificity of ultrasound in diagnosing midgut volvulus are 50% and 100%, respectively. The sensitivity and specificity of UGI series in diagnosing intestinal malrotation are 96.3% and 99%, respectively. Conclusion: Ultrasound and UGI series were valuable imaging methods in diagnosing midgut volvulus/intestinal malrotation. Combining these imaging modalities should be used to increase diagnostic efficiency.
Keywords: Ultrasound, UGI series, midgut volvulus, intestinal malrotation.